Genesis, source, and enrichment factors of helium in Qingyang gas field, Ordos Basin - Yue Chen; Shizhen Tao; Jianrong Gao; Yiqing Yang; Rui Kang; Yanyan Chen; Xiangbai Liu (Energy Exploration & Exploitation, 2025)
Helium is a strategic and scarce resource. The enrichment mechanism of helium-rich gas reservoirs has become a research hotspot in the global energy field. This article takes the Qingyang gas field in the Ordos Basin as a case study. Through analyzing the components of natural gas and noble gas isotope ratios by geochemical means, in combination with the study of the key controlling parameters of helium generation in helium source rocks, the origin of helium gas, the enrichment mechanism, and the geological controlling factors are systematically revealed. The research findings are as follows: (1) The helium content in the Qingyang gas field varies between 0.073% and 0.16%, the average content is 0.095%, and the helium isotope ratio 3 He/ 4 He is between 2.50 × 10 −8 and 3.85 × 10 −8 , showing that the helium is typical of crustal origin; (2) Although the helium generation rate of the Archean basement is lower than that of bauxite, due to its ancient geological age, wide distribution area, and massive thickness, the amount of 4 He accumulated during the long-term geological evolution is 1582 times, 3646 times, and 13,664 times that of mudstone, bauxite, and sandstone, respectively, making it a superior helium source rock; (3) The erosion of the Lower Paleozoic caused direct contact between the Upper Paleozoic strata and the basement, forming a short-distance migration channel. Although it restricts the extraction of helium by gas–water interaction, its near-source accumulation characteristics are important for helium enrichment.